The impact of economic inflation on the growth and development of small and medium enterprises (SMEs) in Iran - Chiani, Faramarz (International Journal of Business Management and Entrepreneurship, 2022)
Purpose: An increase in the prices level has relatively large negative consequences for the economy. When the salary of the labors force does not match the inflation rate of the retail prices, the purchasing power of the labor force will decrease, in addition, as the prices of goods continues to increase, the demand of the labors force for an increase in wages will lead to an increase in the cost of labors and as a result to a decrease in the earned profit which is carried out by economic enterprises and businesses. Therefore, the purpose of this research is to consider of the negative impact of economic inflation on the growth and development of small and medium enterprises (SMEs) in Iran has been investigated. The research is applied research and the method of data collection is descriptive. Methodology: The statistical data was collected using a self-made professional questionnaire and the collected data was processed by SPSS software and used for analysis and conclusions. Iran is the city of Tehran. The statistical sample in this study includes 384 people who were selected based on the Krejcie & Morgan table. Regression model was used to analyze the statistical data in this research. Findings: The results obtained by analyzing the data from the software clearly show that high economic inflation has had a negative impact on the growth and development of small and medium-sized companies.